The Effect of Capital Intensity, Litigation Risk, Profitability, Cash Flow, Institutional Ownership, and Company Size on Accounting Conservatism - Safira, Nur Intan; mursidah, mursidah; Indrayani, Indrayani; Yunina, Yunina (Department of Accounting, Faculty of Economics & Business, 2024)
This study aims to examine the effect of capital intensity, litigation risk, profitability, cash flow, institutional ownership, and company size on accounting conservatism. The population of this study was BUMN companies listed on the Indonesia Stock Exchange (BEI) from 2017 to 2022. Samples were collected using the purposive sampling method, and 14 companies were sampled with an observation period of 6 years, resulting in 84 observations. The research method employed a quantitative approach with data analysis techniques using classical assumption tests. Hypothesis testing was conducted using panel data regression methods with the assistance of the EViews ver.12 program. The results of this study indicate that capital intensity had a positive but insignificant effect on accounting conservatism. Litigation risk had a significant positive effect on accounting conservatism. Profitability had a negative and significant effect on accounting conservatism. Cash flow had a significant positive effect on accounting conservatism. Institutional ownership had a positive but insignificant effect on accounting conservatism. The size of the company had a negative and significant effect on accounting conservatism.